(untitled) (Iranian Journal of Kidney Diseases, 2024)
Introduction. Shenqi pill (SQP) can be used to treat various kidney related diseases, but its exact mechanism of action remains unclear. We intended to analyze the role and mechanism of SQP on renal interstitial fibrosis (RIF). Methods. After performing unilateral ureteral obstruction (UUO) surgery following the Institutional Animal Care and Use Committee guidelines, all rats were assigned into the sham group, UUO group, UUO + SQP 1.5 g/kg, UUO + SQP 3 g/kg, and UUO + SQP 6 g/kg groups. After treatment with SQP for 4 weeks, the appearance of kidney, serum creatinine (SCr), and blood urea nitrogen (BUN) levels were monitored in each group. The pathological injury, extracellular matrix (ECM), and Notch1 pathway-related protein levels were measured using H&E staining, Masson staining, immunohistochemistry, and Western blot, respectively. Results. SQP could obviously ameliorate the appearance of the kidney as well as the levels of SCr and BUN in UUO rats (SCr: 67.6 +/- 4.64, 59.66 +/- 4.96, 48.76 +/- 4.44, 40.43 +/- 3.02 um for UUO, low, medium, and high SQP treatment groups; BUN: 9.09 +/- 0.97, 7.72 +/- 0.61, 5.42 +/- 0.42, 4.24 +/- 0.34 mM for UUO, low, medium, and high SQP treatment groups; P less than .05). SQP also effectively mitigated renal tissue injury in UUO rats (P less than .05). Moreover, we uncovered that SQP significantly inhibited Collagen I, alfa-SMA, Collagen IV, TGF-B1, Notch1, and Jag1 protein expressions in UUO rats kidney (P less than .05). Conclusion. Our data elucidated that SQP can alleviate RIF, and the mechanism may be related to the Notch1/Jag1 pathway. DOI: 10.52547/ijkd.7703